DAS PRIMEIRAS NOÇÕES DE SIGNO AOS PLANOS DA LINGUAGEM NA SEMIÓTICA GREIMASIANA: FROM THE FIRST NOTIONS OF SIGN TO THE PLANES OF LANGUAGE IN GREIMASIAN SEMIOTICS - Castro, Carolina Mazzaron de (2023)
In this article, we will present a theoretical-methodological perspective of the notions around the concept of sign that later refer to the notion of language planes in Discourse Semiotics. We will take a diachronic approach to central notions of the sign from the late nineteenth and twentieth centuries to Greimas’ first conceptions of language planes. Thanks to the real synchronic perspective given to pre-Saussurean studies, the methodological framework postulated by Saussure made it possible to surpass the comparison between languages and influenced the general meanings of linguistics as science in the twentieth century. The language planes in Discourse Semiotics emerged when Greimas defined as signified the signification comprised by the signifier (in which the existence of one element presupposes the other) and concluded that the signification does not depend on the nature of the signifier by which it manifests itself.